Dosimetric comparison of flattened and unflattened beams for stereotactic ablative radiotherapy of stage I non‐small cell lung cancer. Issue 3 (24th February 2014) - Hrbacek, Jan; Lang, Stephanie; Graydon, Shaun N.; Klöck, Stephan; Riesterer, Oliver
Abstract : Purpose: : To compare contribution and accuracy of delivery for two flattening filter free (FFF) beams of the nominal energy 6 and 10 MV and a 6 MV flattened beam for early stage lung cancer. Methods: : For each of 11 patients with stage I nonsmall cell lung cancer three volumetric modulated arc therapy plans were prepared utilizing a 6 MV flattened photon beam (X6FF) and two nonflattened beams of nominal energy 6 and 10 MV (X6FFF, X10FFF). Optimization constraints were set to produce dose distributions that meet the criteria of the RTOG‐0915 protocol. The radiation schedule used for plan comparison in all patients was 50 Gy in five fractions. Dosimetric parameters of planning target volume (PTV) and organs‐at‐risk and delivery times were assessed and compared. All plans were subject to verification using Delta 4 unit (Scandidos, Sweden) and absolutely calibrated gafchromic films in a thorax phantom. Results: : All plans had a qualitatively comparable outcome. Obtained dose distributions were conformal (CI < 1.17) and exhibited a steep dose fall‐off outside the PTV. The ratio of monitor units for FFF versus FF plans in the authorsˈ study ranged from 0.95 to 1.21 and from 0.93 to 1.25 for X6FFF/X6FF and X10FFF/X6FF comparisons, respectively. The ratio systematically increased with increasing size of the PTV (up to +25% for 150 cm 3 PTV). Yet the integral dose to healthy tissue did not follow this trend. Comparison of cumulative dose volume histograms for a patientˈs body showed that X6FFF plans exhibit improved conformity and reduced the volume of tissue that received more than 50% of the prescription dose. Parameters related to dose gradient showed statistically significant improvement. CI50%, CI60%, CI80%, and CI100% were on average reduced by 4.6% ( p < 0.001), 4.6% ( p = 0.002), 3.1% ( p = 0.002), and 1.2% ( p = 0.039), respectively. Gradient measure was on average reduced by 4.2% ( p < 0.001). Due to dose reduction in the surrounding lung tissue, the V 20 Gy and V 12.5 Gy were reduced by 5.5% ( p = 0.002) and 4.5% ( p < 0.001). These dosimetric improvements in the fall‐off were not observed for the X10FFF plans. Differences in sparing of normal tissues were not found to be statistically significant for either of the two FFF beams. Mean beam‐on times were 111 s (2SD = 11 s) for X10FFF, 128 s (2SD = 19 s) for X6FFF, and X6FF plans required on average 269 s (2SD = 71 s). While the mean dose rate was 1555 ± 264 and 1368 ± 63 MU/min, for X10FFF and X6FFF, plans using the conventional X6FF were delivered with the constant maximum dose rate of 600 MU/min. Verification of all plans showed acceptable and comparable results for all plans in homogeneous as well as heterogeneous phantoms. Mean GS (3%, 2 mm) using the Delta 4 phantom were 98.9% (2SD = 3.2%), 99.2% (2SD = 2.3%), and 99.2% (2SD = 2.3%) for X6FFF, X6FF, and X10FFF modalities. Verification using a thorax phantom showed GS > 98% in all cases. Conclusions: : The use of FFF beams for stereotactic radiation therapy of nonsmall cell lung cancer patients yielded dose distributions qualitatively comparable to flattened beams and significantly reduced treatment delivery time. Utilizing the X6FFF beam improved conformity of dose distribution. On the other hand, X10FFF beam offered a slight improvement in treatment efficiency, and lower skin and peripheral dose. All effects were relatively small.